Experimental study on crack features of steel fiber reinforced concrete tunnel segments subjected to eccentric compression. (December 2020) - Xu, Haiyan; Wang, Zhijie; Shao, Zimeng; Jin, Hesong; Li, Zhen; Jiang, Xinzheng; Cai, Libin
Graphical abstract: Highlights: Crack features of steel fiber reinforced concrete segments subjected to eccentric compression are studied. Two crack patterns are observed and summarized, which are different from that of reinforced concrete. The change of crack length and width of steel fiber reinforced concrete specimens with magnitude of eccentricity is investigated. Abstract: This paper studies crack features of steel fiber reinforced concrete (SFRC) tunnel segments subjected to eccentric compression. An experiment is conducted in which 56 SFRC beam specimens of different steel fiber type and dosage are cast and loaded. Both qualitive observation and quantitative analysis are made to shed light on crack features of SFRC beams which are demonstrated by crack patterns, the development of crack width and length as well as the energy absorbed during the cracking process. Based on the cracking features of SFRC tunnel segment under eccentric compression obtained in this paper, an improved design method applicable to the SFRC tunnel segment is proposed. The results show that: (1) Two different crack patterns would occur for SFRC beams under compressive loads of different eccentricity, which is different from that of reinforced concrete (RC) beams, and the two patterns differ in how cracks gradually develop. (2) SFRC beam specimens are safer when subjected to compressive loads of small eccentricity. Dramix 5D SFRC tunnel segments are more suitable for loads of smaller eccentricity (0.1 m) since it exhibits better anti-cracking capacity in that scenario. (3) The Boltzmann fitting formula can properly reflect the development of crack length with the increase of the crack width. (4) Using the obtained experimental results, the rationality of the improved design method is well verified.